A look at the radio show “ondas” in san andres island: pedagogical and social contributions - Duarte Torres, Paula Andrea; Hernández Vásquez, Jenifer C; Medina, Jairo Humberto (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The present paper reports the evaluation of the social and the pedagogical impact of the radio show “Ondas” in San Andres Island, which promotes a culture of science, technology, and innovation in children, teenagers, and youth. This evaluation was conducted in 2011 by a fieldwork in seven educational institutions of the island, where through three lines of analysis (coverage, educational and social) the process results are presented. The first line of analysis focuses on the characteristics of the actors linked to the radio show, the second and third lines present the findings and reflections on the contributions of “Ondas” in terms of learning, actors’ participation, and linking family and community to the process. In the same way recommendations to strengthen the radio show in the department are offered.